Early discontinuation of the IMPLANON® and associated factors in Ethiopia, systematic review and meta-analysis - Zerihun Figa; Tesfaye Temesgen Chekole; Dessalegn Tarekegn; Abbas Ahmed Mahamed; Etaferahu Bekele (Heliyon, 2023)
Background: Implanon® is a commonly used effective long-acting reversible contraceptive method. It provides contraception for up to three years. Its early discontinuation was associated with an unwanted pregnancy, abortion, and socioeconomic burden. Thus, the main aim of this systematic review and meta-analysis is to determine the rate of early discontinuation of Implanon® and associated factors in Ethiopia. Method: This Systematic review and meta-analysis was performed by using online databases including PubMed, Google Scholar, Cochrane, HINARI, Web of Science, and other gray and online repositories of Ethiopian Universities. The JOANNA Briggs Institute standard data extraction and appraising sheet format was used for the extraction of all included studies. To test the heterogeneity of the studies the Cochran Q test and I2 statistics test were used. The Funnel plot and Egger's tests were used to detect possible publication biases of the included studies. The forest plots were used to present the finding of the overall prevalence of the early Implanon® discontinuation and the odds ratio (OR) along with a 95% CI. Result: In this systematic review and meta-analysis seven studies with a total population of 3161 women using Implanon® were included. The overall pooled early Implanon® discontinuation rate was 31.34% (95%CI: 19.20, 43.47). Early discontinuation of Implanon® was associated with lack of counseling during service delivery 2.55times (OR: 2.55, 95%CI: 1.99, 3.25), the experienced side effect 3.25 times (OR: 3.25, 95%CI: 2.48, 4.24), absence of appointment after insertion 6.06 times (OR: 6.06, 95%CI: 2.15, 17.05), others decision on the women's choice 3.30 times (OR = 3.30, 95%CI: 2.52, 4.32), and lack the satisfaction of provided service 2.68 times (OR: 2.68, 96%CI: 1.61, 4.45). Conclusion: About one-third of the women in Ethiopia discontinue the use of Implanon® within one year of the insertion. This is high compared to findings from other countries. Lack of counseling about the service, women's experience of the side effect, absence of the appointment following the service provision, other decisions on the method chosen, and lack of satisfaction were factors associated with the discontinuation of Implanon®. Hence, efforts should be made to reduce the rate of early discontinuation of Implanon® through drafting national guidelines and strategies accompanied by appropriate implementation, follow-up to foster adequate counseling, arrangement of appointments, helping women to decide on the choice, and increase the quality of care provision to enhance the satisfaction of the service.